2014
DOI: 10.1155/2014/453924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber Content on Abrasive Wear Behavior of Date Palm Leaf Reinforced Polyvinyl Pyrrolidone Composite

Abstract: The effect of fiber contents on wear behavior of date palm leaf reinforced polyvinyl pyrrolidone (PVP/DPL) composites has been experimentally investigated. The test samples with fillers in 10, 20, 30, and 40% based on weight of fibers were prepared using injection molding. The optimum fiber content (i.e., 26 wt%) for maximum mechanical strength of the composites was determined by regression analysis. The dry sliding wear tests were conducted for each composition at different sliding velocities (0.392, 0.471, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…6 ). Similar to the study of 92 who studied the wear behaviour of polyvinyl pyrrolidone composite incorporated with date palm leave fiber. It was observed in the study that weight loss reduced with fiber loading irrespective of the load applied during test.…”
Section: Resultsmentioning
confidence: 78%
“…6 ). Similar to the study of 92 who studied the wear behaviour of polyvinyl pyrrolidone composite incorporated with date palm leave fiber. It was observed in the study that weight loss reduced with fiber loading irrespective of the load applied during test.…”
Section: Resultsmentioning
confidence: 78%
“…Several studies investigated green fillers including natural fibers, olive husk and almond shells. 4 -7 More work in the literature has reported that special kinds of organic fillers, such as talc and tamarind kernel powder, are frequently used to enhance the mechanical properties and reduce the composite cost. 8,9 Bensalah et al studied polypropylene (PP) hybrid composites based on a mixture of graphite and clay.…”
Section: Introductionmentioning
confidence: 99%
“…This causes debonding of fiber from the epoxy matrix. Thus, at higher fiber loading, the interfacial adhesion between the matrix and fiber is not adequate enough to resist the sliding force resulting in higher wear .…”
Section: Resultsmentioning
confidence: 99%